2014
DOI: 10.1007/s12031-014-0467-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of cAMP-Dependent Protein Kinase A Activity in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier

Abstract: Our previous studies demonstrated that low-dose endothelial monocyte-activating polypeptide-II (EMAP-II) can selectively increase the permeability of blood-tumor barrier (BTB). In addition, low-dose EMAP-II significantly decreases the cyclic adenosine monophosphate (cAMP) concentration and the protein kinase A (PKA) expression level in tumor tissues in the rat C6 glioma model. In this study, an in vitro BTB model was used to investigate the potential role of cAMP/PKA signaling cascade in EMAP-II-induced BTB hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 39 publications
8
14
0
Order By: Relevance
“…In our previous and the present studies, the EMAP-II concentration used to induce opening of the BTB was 0.05 nM (Xie et al 2012;Li et al 2012Li et al , 2015. However, as a proinflammatory cytokine, EMAP-II might be toxic to the RBMECs.…”
Section: Emap-ii Has No Effect On Cell Viability In Rbmecsmentioning
confidence: 49%
See 4 more Smart Citations
“…In our previous and the present studies, the EMAP-II concentration used to induce opening of the BTB was 0.05 nM (Xie et al 2012;Li et al 2012Li et al , 2015. However, as a proinflammatory cytokine, EMAP-II might be toxic to the RBMECs.…”
Section: Emap-ii Has No Effect On Cell Viability In Rbmecsmentioning
confidence: 49%
“…Data from our recent study revealed that increased intracellular cAMP nearly completely blocked EMAP-II-induced BTB hyperpermeability in EMAP-IItreated BTB RBMECs. Additionally, elevated cAMP prevented EMAP-II-induced increase in RhoA/ROCK activity (Li et al 2015). PKA activation only partially attenuated the effects of EMAP-II, which suggests the involvement of a cAMP/PKA-independent signaling pathway.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations